Improvement of Soybean Processing Technology and Safety Criteria - Sohibjonovich, Muhammadjonov Avazbek; Usmonovich, Khakimov Mukimjon (European Journal of Life Safety and Stability (2660-9630), 2021)
The article aims to improve the processing technology and safety criteria for growing soybeans. Since soy processing can be used to produce oil, confectionery, and even pharmaceuticals, the issues of improving them have been discussed.